An evaluation of the association between specific post‐overdose care services in emergency departments and subsequent treatment engagement. Issue 1 (11th January 2023) - Chambers, Laura C.; Hallowell, Benjamin D.; Samuels, Elizabeth A.; Daly, Mackenzie; Baird, Janette; Beaudoin, Francesca L.
Abstract: Objective: The objective of this study was to estimate the association between receipt of specific post‐overdose care services in the emergency department (ED) and subsequent engagement in treatment for opioid use disorder (OUD) after discharge. Methods: This was a retrospective cohort study of Rhode Island residents treated at 1 of 4 EDs for opioid overdose who were not engaged in OUD treatment and were discharged home (May 2016–April 2021). Electronic health record data were used to identify ED services received, and state administrative data were used to define subsequent engagement in OUD treatment within 30 days. Multivariable conditional logistic regression was used to estimate the association between ED services received and subsequent treatment engagement. Results: Overall, 1008 people not engaged in OUD treatment were treated at study EDs for opioid overdose and discharged home, of whom 146 (14%) subsequently engaged in OUD treatment within 30 days. Most patients were aged 25 to 44 years (59%) and non‐Hispanic White (69%). Receipt of behavioral counseling in the ED (adjusted odds ratio [aOR] = 1.79, 95% confidence interval [CI] = 1.18–2.71) and initiation of buprenorphine treatment in/from the ED (aOR = 5.86, 95% CI = 2.70–12.71) were associated with treatment engagement. Receipt of a take‐home naloxone kit or naloxone prescription and referral to treatment at discharge were not associated with treatment engagement. Overall, 49% of patients received behavioral counseling in the ED, and 3% initiated buprenorphine in/from the ED. Conclusion: Strategies for increasing provision of behavioral counseling and initiation of buprenorphine in the ED may be useful for improving subsequent engagement in OUD treatment after discharge.